HUSBAND SUPPORT AND COPING MECHANISM ON PATIENT OF REPRODUCTIVE SYSTEM CYST - Partinah Partinah; Siti Rofi'ah (Jurnal Riset Kesehatan, 2020)
The reproductive health problems can result in impaired function of the reproductive organs in the form of decreased fertility, even difficulty getting the pregnancy process can occur, causing psychological impacts on women. Husband's support can help the healing process because it refers to a comfort, concern, self-esteem or help for reproductive system cysts. The purpose of this study was to determine the relationship between husband's support and coping mechanisms of reproductive system cysts. This type of correlational analytic research with cross sectional approach. The population of this study were all patients with reproductive system cysts who were treated at Tidar Hospital, Magelang City during March-May 2020, using accidental sampling technique as many as 15 respondents. Data analysis used the Spearman rank test. The results showed that there was a relationship between husband's support and coping mechanisms in patients with reproductive system cysts in Tidar Hospital, Magelang City (p value=0.002 less than α=0.05), with moderate closeness (r=0.591). Husband are expected to take full responsibility for their wives, both healthy and sick, and midwives are more sensitive to the patient's psychological condition, including coping mechanisms.